Gender Implications of the Introduction of Forage Chopper Machines in Babati, Tanzania - International Institute of Tropical Agriculture; International Livestock Research Institute (International Food Policy Research Institute, 2018)
In 2015, livestock scientists implementing Africa RISING research-in-development activities (R-in-D) introduced forage chopper machines in seven villages in Babati District, northern Tanzania. The dataset included in this study was generated from the research conducted an year later to understand the gender implications of the new processing practices. The survey was conducted among households who used forage chopper machines and included questions about intra-household decision-making, previous knowledge of the technology, training, and willingness to pay among many others. Altogether 53 male and female respondents were selected for the survey.